PENGARUH WAKTU INKUBASI DAN KONSENTRASI SUKROSA TERHADAP KARAKTERISTIK MINUMAN PROBIOTIK DARI WHEY HASIL SAMPING KEJU - Nurhartadi, Edhi; Nursiwi, Asri; Utami, Rohula; Widayani, Erina (Jurnal Teknologi Hasil Pertanian, 2018)
lactose, proteins and minerals. This study aims to determine the effect of variations in incubation time andsucrose concentration on the probiotic drink characteristics made from whey. This study uses CompletelyRandomized Design (CRD) with two factors, variation of incubation time (24 and 36 hours) and sucroseconcentration of (8%; 10%; 12%) on the probiotic whey drink. Probiotic starter cultures used are Lactobacillusacidophillus and Bifidobacterium longum IFO ATCC 13951 15 708 with ratio of 1: 1. Analysis was performedon viscosity, lactic acid levels, pH, antioxidant activity, total lactic acid bacteria and sensory characteristics.The results showed that the selected formula based on hedonic test is probiotic whey drink with 36-hourincubation time and 12% sucrose concentration. Probiotic whey drink has characteristics namely viscosity 6.578cP, 0.453% lactic acid levels, pH 4.36, the antioxidant activity of 19.409%, and total lactic acid bacteria 7.4 x109 cells / ml.